Evaluasi 36 Genotipe Padi Gogo Terhadap Cekaman Biotik Dan Abiotik Pada Enam Lokasi Berbeda: Evaluasi 36 Genotipe Padi Gogo Terhadap Cekaman Biotik Dan Abiotik Pada Enam Lokasi Berbeda - Yashanti Berlinda Paradisa; Sri Indrayani; Heru Wibowo; Ambar Yuswi Perdani; Dody Priadi; Puspita Deswina; Eko Binnaryo Mei Adi; Enung Sri Mulyaningsih; Yuli Sulistyowati; Yuliana Galih Dyan Anggraheni; Fiqolbi Nuro (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Biotic and abiotic stress during cultivation is one of the challenges in increasing upland rice production. Stress can be mild to severe, potentially reducing yield. Knowing the ability of plants to adapt to stressful environments from the start is essential information in the assembly of new high-yielding varieties. This study aims to determine stress in 36 upland rice lines and the adaptability of several upland rice lines to environmental stress. The genetic material used was 36 upland rice lines and two comparison varieties with four replications. The line is planted in Lampung, DI. Yogyakarta and East Java, two locations each. That area has different soil types and elevations. Data were analyzed descriptively and tabulated. In addition, the average scoring of biotic and abiotic stress for each location was calculated. The results showed that biotic stresses found in the plantations were Leaf Blast, Neck Blast, Bacterial Leaf Blight, Brown Spot, Red Striped, Rats, Birds, Rice Leaf Roller, and Stem Borer. Meanwhile, the abiotic stresses found were drought and salinity. From 36 tested lines, it showed that G26 was resistant to biotic stress caused by pests and diseases, G29 was drought-tolerant, and G6 was salinity tolerant.